2022
DOI: 10.1002/edn3.300
|View full text |Cite
|
Sign up to set email alerts
|

Urban environments harbor greater oomycete and Phytophthora diversity, creating a bridgehead for potential new pathogens to natural ecosystems

Abstract: Anthropogenic activities contribute to changes in the range and distribution of species. Globalization is resulting in human‐mediated dispersal that is causing a breakdown in normal biogeographic barriers. But the impact of anthropogenic activities on plant pathogen communities is still poorly understood. We conducted an eDNA metabarcoding study to compare communities of oomycetes, a group of eukaryotic microorganisms that comprises important crop and tree pathogens, in urban, natural, and interface environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 133 publications
2
16
0
Order By: Relevance
“…It has previously been demonstrated that urban environments and botanical gardens act as a bridgehead for Phytophthora invasions, providing a suitable environment for species to become established and then spread to newly encountered hosts (Hulbert et al, 2019; Paap et al, 2017). The number of species established in natural systems is more limited due to environmental filtering perhaps linked with healthier soils and more resilient environment (Dale et al, 2022; Redondo et al, 2018). The temperature range for mycelial growth and the growth rate at optimal temperature were also important traits influencing tolerance to temperature extremes and ability to rapidly colonize suitable substrate.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that urban environments and botanical gardens act as a bridgehead for Phytophthora invasions, providing a suitable environment for species to become established and then spread to newly encountered hosts (Hulbert et al, 2019; Paap et al, 2017). The number of species established in natural systems is more limited due to environmental filtering perhaps linked with healthier soils and more resilient environment (Dale et al, 2022; Redondo et al, 2018). The temperature range for mycelial growth and the growth rate at optimal temperature were also important traits influencing tolerance to temperature extremes and ability to rapidly colonize suitable substrate.…”
Section: Discussionmentioning
confidence: 99%
“…were not yet reported or are still regulated species (Anonymous, 2016;Charron et al, 2022;Dale et al, 2022;Feau et al, 2019). However, although the resolution of metabarcoding data is sufficient for many species, care must be taken when inferring the distribution of species belonging to specific clusters or complexes for which the resolution does not allow discrimination between species in the said group or cluster.…”
Section: F I G U R Ementioning
confidence: 99%
“…Among the genus of particular interest, 26 clusters or complexes of Phytophthora species were found, confirming the genus's remarkable diversity and ability to adapt to various natural and anthropogenically disturbed environments. However, with 40 species or complexes identified, the genus Pythium was the most diverse, as it is often the case in several natural, urban, and agricultural environments (Cerri et al, 2017;Dale et al, 2022;Fiore-Donno & Bonkowski, 2021;Navarro et al, 2021;Sapp et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…The dispersal of Phytophthora from an initial point of establishment, such as gardens, parks or conservation areas, further into natural forest environments seems to happen through a combination of several factors. Urban environments often function as bridgeheads for invasion by harbouring many exotic species and acting as their first point of contact with the new environment (Dale et al, 2022;Paap et al, 2017). Phytophthora inoculum can be transported in soil, living plants or water.…”
Section: Introductionmentioning
confidence: 99%